Delay and backlog control of aggregation systems for wireless communications. Issue 2 (2020) - Georges, Jean-Philippe; Divoux, Thierry; Breck, Damien
Abstract: The aggregation system implemented in wireless communication networks aims to optimize the network efficiency regarding the encapsulation information and the medium access mechanisms. This paper proposes to evaluate the performances of such (A-MSDU like) system from a dedicated frame point of view, which is important in order to predict the Quality of Service offered to a client or to an application. Regarding the incoming flows, enabling or disabling the aggregation system, and tuning in real time the aggregate size, makes possible to satisfy both the users' requirement and the network provider efficiency. In the case of voice or video class wireless communication where some loss of data is acceptable, numerous simulations using Riverbed Modeler led to express several recommendations embedded in an algorithm which sets dynamically the aggregation parameters in order to adjust it to the incoming traffic.